Homocysteine and Stroke: A 30-Year Bibliometric Study Uncovering Research Trends and Future Directions - Loo Keat Wei; Saras Menon; Lyn R. Griffiths (Journal of Mind and Medical Sciences, 2025)
Recent years have seen a rapid expansion in research examining the relationship between homocysteine and stroke. In this study, we conducted a comprehensive bibliometric analysis of 233 articles related to homocysteine and stroke, published over the past 30 years in the Web of Science Core Collection. Our findings reveal a significant global increase in research on homocysteine and stroke, with China emerging as a leader, representing 39.9% of the total publications. Employing advanced methodologies such as co-citation analysis, bibliographic coupling, keyword co-occurrence, and citation burst analysis, we identified key research themes and emerging trends within the field. Notably, the results indicate a shift in focus from viewing homocysteine solely as a biomarker to recognizing its potential role in stroke prevention and management. These insights provide a valuable roadmap for future research directions and clinical strategies aimed at enhancing stroke prevention and improving patient outcomes.